“ Frankish” or “ Byzantine” Saint? The Origins of the Cult of Saint Martin in Dalmatia - Trpimir Vedriš (2009)
Departing from the traditional historical narrative that the areas along the eastern Adriatic coast were under Byzantine rule from, at least the age of Justinian until the late eleventh century – author focuses on the local hagiotopography in order to address the problem of the chronological layers of the cult of St Martin of Tours and the directions of its dissemination in the region. Critically assessing the “ Carolingian thesis” according to which the cult of was introduced in Dalmatia only by the Franks in the ninth century, the author reconstructs more complex picture in which substantial importance is given to the lasting results of Justinian’ s reconquista. As the result, Frankish promotion of the cult is seen as yet another aspect of a Carolingian renovatio which actually preserved many features of cultural and religious continuity.
Projekt MZOS
ENG